Designing a Web-Based Career System Using the Laravel Framework using the waterfall method - Khaliq, Abdul; Batubara, Supina; Syaula, Maya; Sahrial, Sahrial (International Conference on Sciences Development and Technology, 2022)
Rapid advancements in data and communication technology are evident, especially when it comes to data's crucial role in modern life. The internet serves as the primary medium for data transmission, facilitating easy access to information like job vacancies through specialized websites. Without data, securing desirable opportunities, such as employment, would prove exceedingly challenging. As professions significantly impact individuals' lives, obtaining relevant professional data can be arduous for some, while simultaneously, industries may struggle to swiftly find suitable employees possessing the required skills. To address this issue, a web-based job vacancy application called a web search program was developed using the waterfall method, utilizing PHP programming language and MySQL database. This application aims to simplify the process of job seekers finding relevant job vacancy data while assisting industries in promptly identifying skilled candidates who match their requirements.